A educação física e o livro didático : para democratizar a cultura corporal - Melo, Fernando Garcez de (2021)
The inclusion of physical education in the National Book and Teaching Material Program (PNLD), in 2017, was the reason for this investigation. Traditionally, textbooks are important and impactful in the most diverse curriculum components of basic education, although there are controversies. In the case of physical education, its absence from this program for 32 years raises doubts about the value of this material, and if contributions will be provided. From this context, I set myself the objective of evaluating its inclusion in the PNLD. However, still in the exploration phase of the subject, I noticed that, instead of directing attention to its evaluation strictly in the field/references of public policy, it seemed pertinent to stick to the question: textbook for which type of physical education? What made me reflect on physical education itself, leading me to discussions about its purpose at school. The investigative/methodological strategy chosen — much more an inspiration than the adoption of a set of procedures — was the pragmatism of Richard Rorty. With this resource in hand, I indicated how physical education is intertwined with a notion of knowledge as representation, making it direct a significant effort to find/manufacture its object that would also bring it legitimacy; and I explored the idea of adopting a non-representationalist notion of knowledge, an idea that I indicated by contrasting a physical education aimed at epistemology and one aimed at the democratization of body culture. With that, I wanted to suggest that the textbook will be more relevant as it contributes to this democratization. In what followed, I sought to indicate also how the textbook is repeatedly described as containing The Word. Whereas, a better way to deal with it is to take it as a profusion of narratives. In addition to this context, primarily registered in academic literature, I investigated the school context. To do so, I visited sixteen municipal schools in Cuiabá/MT, in the second half of 2019, and interviewed a teacher from each unit. The teachers narrated and collaborate in understanding how the implementation of the physical education teaching collections occurred, referring to the PNLD/2019. The purpose of listening to them was not to find the focal point of what happened but to address the diversity of events, to be sensitized to the challenges. Thus, it is worth noting how problematic the implementation was, especially in relation to the choice process. Despite the obstacles, there are professors who evaluate and put the available collections to good use. And the evaluative scenario is not complete here. Having addressed more general topics and building bridges with the school context, I highlight how physical education has, in recent decades, been dedicated to the purpose of democratizing body culture and exploring textbooks as a useful tool. Despite the difficulties, somewhat predictable for being the first year of inclusion of physical education in the PNLD, there is a promising scenario for exploring this tool. By following Rorty's clues, I think that the issue was not so much to prove or disprove the relevance of inserting physical education in the PNLD, but to create a promising scenario, in which future results would compensate for the effort in the present. I understand that, by getting rid of what I called the epistemic obstacle, we will open up new possibilities for more fruitful and interesting ways to develop physical education, which includes the exploration of textbooks (a resource for a long time distant from the area for reasons that were previously internal to that external). Therefore, the thesis is that physical education can be associated with the PNLD to democratize body culture.